2013
DOI: 10.1097/sla.0b013e31828c8a30
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Nomogram for Prediction of Recurrence in Desmoid Fibromatosis

Abstract: Objective To construct a postoperative nomogram to estimate the risk of local recurrence for patients with desmoid tumors. Background The standard management of desmoid tumors is resection, but many recur locally. Other options include observation or novel chemotherapeutics, but little guidance exists on selecting treatment. Methods Patients undergoing resection during 1982-2011 for primary or locally recurrent desmoids were identified from a single-institution prospective database. Cox regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
224
5
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(244 citation statements)
references
References 31 publications
9
224
5
6
Order By: Relevance
“…On the one hand, younger patients presented with a higher risk of local recurrence both in our series and in other previous reports. 8,9,13 On the other hand, we observed that some patients' lesions ceased to grow and even shrank spontaneously after reaching 50 or 60 years of age, although these lesions relapsed frequently after resection in the same individuals when they were in their 20s and 30s. These phenomena remain confusing, but speculation reveals some possible reasons.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…On the one hand, younger patients presented with a higher risk of local recurrence both in our series and in other previous reports. 8,9,13 On the other hand, we observed that some patients' lesions ceased to grow and even shrank spontaneously after reaching 50 or 60 years of age, although these lesions relapsed frequently after resection in the same individuals when they were in their 20s and 30s. These phenomena remain confusing, but speculation reveals some possible reasons.…”
Section: Discussionmentioning
confidence: 70%
“…7,8,17,18 Two recent studies with large patient samples obtained different results. In the first study, Zeng et al 7 recruited 233 consecutive DF patients who underwent macroscopically complete resection, and the authors concluded that R1 resection status was a factor associated with worse 16 believed that some of the "close but negative" margins were actually "positive" and that an inadequate sampling of surgical resection margins for the pathologic assessment of margin status may explain why resection margins fail to predict the risk of local recurrence in many previous studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The National Comprehensive Cancer Network (NCCN) guidelines suggest observation of these tumors unless symptomatic or causing impairment of organ function, therapy then is chosen based on the location and potential resulting morbidity of the procedure [22,23]. There has been no consensus on the surgical margin requirements when performing desmoid resections, some studies have clearly shown that an R1 margin is an independent risk factor for local recurrence while other studies showed no difference between R0 and R1 resections if patients are closely followed [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The reported results about the importance of age, location, resection margins, and adjuvant radiotherapy are conflicting. 4,7,[10][11][12] Also, radiotherapy has been widely applied for DT, both in primary and adjuvant settings. Results have been ambiguous, especially for adjuvant radiotherapy.…”
mentioning
confidence: 99%